Couple of doubts

I am facing problem in solving these differential equation

1) \(\large{\frac{d^{2}y}{dx^{2}}+e^{2y}(\frac{dy}{dx})^{3}=0}\)

2)d2ydx2+3y=2x\large{\frac{d^{2}y}{dx^{2}}+3y=-2x}

#Calculus

Note by Tanishq Varshney
6 years, 1 month ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

1) is non-linear, so is going to be messy. I'll have a look at 2) though.

The characteristic equation has roots ±i3,\pm i\sqrt{3}, so yc=c1cos(3x)+c2sin(3x).y_{c} = c_{1}\cos(\sqrt{3}x) + c_{2}\sin(\sqrt{3}x).

For the particular solution, letting yp=2x3y_{p} = -\dfrac{2x}{3} will do the trick, and thus the general solution is

y=yc+yp=c1cos(3x)+c2sin(3x)2x3.y = y_{c} + y_{p} = c_{1}\cos(\sqrt{3}x) + c_{2}\sin(\sqrt{3}x) - \dfrac{2x}{3}.

Brian Charlesworth - 6 years, 1 month ago

Log in to reply

sir can u provide me the steps, or any note on how to solve these, actually i only know how to solve homogeneous second order differential equation

Tanishq Varshney - 6 years, 1 month ago

Log in to reply

I'll provide you with a great link, just to save some time. The headings "Complex Roots" and "Nonhomogeneous DE's" are applicable for 2).

For 1) you could try the substitution v=dydx.v = \dfrac{dy}{dx}. The equation then becomes

vdvdy+e2yv3=0,v\dfrac{dv}{dy} + e^{2y}v^{3} = 0, which is still non-linear but is now first-order and may be easier to solve.

Brian Charlesworth - 6 years, 1 month ago

Log in to reply

@Brian Charlesworth For the first one of the terms on the other side and divide by (dydx)3\left(\frac{dy}{dx}\right)^3 on both the sides to get the equation of the form d2xdy2=e2y\displaystyle \frac{d^{2}x}{dy ^{2}} = - e^{2y} which is then trivial.

Sudeep Salgia - 6 years, 1 month ago

Log in to reply

@Sudeep Salgia sorry not understood, how is d2ydx2(dydx)3=d2xdy2\huge{\frac{\frac{d^{2}y}{dx^{2}}}{(\frac{dy}{dx})^{3}}=\frac{d^{2}x}{dy^{2}}}

Tanishq Varshney - 6 years, 1 month ago

Log in to reply

@Tanishq Varshney It is simple. Start with (dxdy)=(dydx)1\left(\frac{dx}{dy }\right) = \left(\frac{dy}{dx}\right)^{-1} . Then differentiate wrt yy and apply chain rule on the other side to get the required answer.

Sudeep Salgia - 6 years, 1 month ago

@Brian Charlesworth thank you so much sir for the help ¨\ddot \smile

Tanishq Varshney - 6 years, 1 month ago

@Brian Charlesworth but sir shouldn't it be vdvdx+e2yv3=0v\frac{dv}{dx}+e^{2y}v^{3}=0

Tanishq Varshney - 6 years, 1 month ago

Log in to reply

@Tanishq Varshney With dydx=v\dfrac{dy}{dx} = v we have, by way of the chain rule, that d2ydx2=dvdx=dvdydydx=vdvdy.\dfrac{d^{2}y}{dx^{2}} = \dfrac{dv}{dx} = \dfrac{dv}{dy}\dfrac{dy}{dx} = v\dfrac{dv}{dy}.

So we've converted the original second-order DE with xx as the independent variable into a first-order DE with yy as the independent variable. We can simplify a bit further by eliminating v=0v = 0 as a solution, giving us

dvdy+e2yv2=0,\dfrac{dv}{dy} + e^{2y}v^{2} = 0, which is separable with solution v=2e2y+C.v = \dfrac{2}{e^{2y} + C}.

So now we have that dydx=2e2y+C,\dfrac{dy}{dx} = \dfrac{2}{e^{2y} + C}, which again is separable with solution e2y2+Cy=2x+K,\dfrac{e^{2y}}{2} + Cy = 2x + K,

where constants CC and KK would be determined from any initial conditions that might be provided. We can't form a "nice" equation in the form y=f(x)y = f(x) from this equation, but we've come far enough. :)

Brian Charlesworth - 6 years, 1 month ago
×

Problem Loading...

Note Loading...

Set Loading...